Understanding the breeding phenology of anadromous fish Tenualosa ilisha (Hamilton, 1822) in relation to climatic variables in Brahmaputra River, India - Borah, Simanku; Sahoo, Amiya Kumar; Gopinathapillai, Vaisakh; Meena, Dharmendra Kumar; Jaiswar, Ashok Kumar; Deshmukhe, Geetanjali; Yadav, Anil Kumar; Gogoi, Pranab; Mohanty, Debasmita; Ramteke, Karankumar; Bhattacharjya, Birendra Kumar; Das, Basanta Kumar (Frontiers in Marine Science, 2023)
The Hilsa, Tenualosa ilisha (Hamilton, 1822) commands a very high value as food fish. The present study was carried out to understand the breeding phenology of T. ilisha in relation to climatic variables. Monthly fish samples were collected from the two landing centres namely, Uzanbazer (Guwahati) and Shri Ramghat, Dhubri in the river Brahmaputra during May 2018 to April 2019. The assessment of gonado-somatic index (GSI) of T. ilisha revealed higher GSI values during October to February, indicating temporal variations with respect to sex. In males, the highest GSI value was observed in the monthJanuary followed by February, while in females, GSI value was found to be highest in the November followed by October. The GSI (pooled) value was negatively correlated with air temperature indicating vulnerability of the species to climate change. The highest percentage of mature males was observed during October-February, and mature females during October-December. Length at first maturity was recorded to be 290 mm for female(s) and 259 mm for male(s). The absolute fecundity ranged from 103,164 to 583,456 ova for fishes in the size range of 229-403 mm, with an average of 250,532 ova per female. Relative fecundity was found to range from 306 -1096 ova per gram body weight, with an average of 791 ova per gram body weight. The diameter of ova of the studied fishes ranged from 414.6 µm to 738.2 µm, with mean value of 546.73 ± 7.18 µm. The percentage frequency distribution of mature ova shows distinct single peak or mode. Sex ratio (Male:Female) was found to be 1:0.87, indicating dominance of males over females. The Chi-Square test on observed sex ratio against the hypothetical ratio of 1:1 did not reveal significant difference (p>0.05). The findings of the present study can provide impetus towards successful management of this highly prized, transboundary and migratory resource of River Brahmaputra, in the context of changing climate.